KARAKTERISASI SIFAT FISIK PRODUK MIE BASAH DARI TEPUNG OPA (Dioscorea esculenta L.) TERMODIFIKASI DENGAN PENAMBAHAN BUBUR RUMPUT LAUT - R, St Rahmi; Wahyuni, Sri; ansharullah, ansharullah (Jurnal Sains dan Teknologi Pangan, 2018)
ABSTRACT Gembili (Dioscorea esculenta L.) is one of the biological resources of tubers that have not been handled properly. Gembili which has the name of Opa region (Wakatobi) contains high carbohydrate so that it has potential as alternative source of non-rice and non-wheat carbohydrates. The purpose of this study was to determine the effect of seaweed porridge addition to physical quality of wet noodle product from Opa flour. This research used Completely Randomized Design (CRD), which consist of formulations M0, M1, M2, M3, M4, M5, M6, and M7 of seaweed porridge. Analysis of physical quality (water absorption, development power, breaking power and cooking time) wet noodle products. The physical quality of the wet noodles from Opa flour with formulations M0, M1, M2, M3, M4, M5, M6, and M7 of seaweed porridge has a water absorption value of 88.13% - 113.5%, power of noodles development ranges from 8.89 % - 33.33%, the breaking strength of noodles is 9.33% - 33.33%. So it can be concluded that the addition of seaweed porridge causes the physical quality of wet noodles from Opa flour better than before. Keywords: Opa flour, wet noodles, seaweed. ABSTRAK Umbi Gembili (Dioscorea esculenta L.) merupakan salah satu sumber daya hayati umbi-umbian yang selama ini belum banyak ditangani sebagaimana mestinya. Gembili yang mempunyai nama daerah Opa (Wakatobi) mengandung karbohidrat tinggi sehingga berpotensi sebagai sumber karbohidrat alternatif non beras dan non terigu. Tujuan penelitian ini untuk menentukan pengaruh penambahan bubur rumput laut terhadap kualitas fisik produk mie basah dari tepung Opa. Penelitian ini menggunakan Rancangan Acak Lengkap (RAL), yang terdiri dari 7 variasi penambahan bubur rumput laut yang disebut sebagai formulasi M0, M1, M2, M3, M4, M5, M6, dan M7. Analisis kualitas fisik (daya serap air, daya pengembangan, daya putus dan lama pemasakan) produk mie basah. Kualitas fisik mie basah dari tepung Opa pada formulasi M0, M1, M2, M3, M4, M5, M6, dan M7 memiliki nilai daya serap air berkisar 88.13% - 113.5%, daya pengembangan berkisar 8.89% – 33.33%, daya putus mie berkisar 9.33% – 33.33%. Sehingga dapat disimpulkan bahwa penambahan bubur rumput laut menyebabkan kualitas fisik mie basah dari tepung Opa semakin baik